Agrarian Question and Democratic Decentralization in Kerala (Agrarian South: Journal of Political Economy, 2017)
This article is dedicated to Professor Sam Moyo, whose work on radical land reform in Zimbabwe within a neoliberal environment has engaged our attention and illuminated the subject of our own research, the agrarian question in post-land reform Kerala. In Kerala, the experiment of democratic decentralization is now nearly two decades old. The present article focuses on one of its weakest links, the failure to generate sustainable livelihood opportunities, in either industry or agriculture. The crisis in agriculture is best seen as part of a larger process of structural transformation of the Kerala economy which has blocked agrarian transition and requires thorough overhauling of the social organization of production for overcoming the present impasse. Even though local governments have a major role in resolving the agrarian question, it presupposes greater involvement of higher tiers of government and deeper cooperation among different tiers